2002
DOI: 10.7863/jum.2002.21.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Sonographic Cervical Length Changes During Normal Pregnancy

Abstract: Our study shows that cervical length is comparable in nulliparous and multiparous women throughout pregnancy. In both groups, it actually shows a progressive, linear reduction between the 10th and 40th weeks. Reference ranges constructed for the whole gestational period might be more useful than a single cut-off value for more efficient prevention and management of preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 18 publications
2
51
0
8
Order By: Relevance
“…Results of other studies are more variable: some found that cervical length did not change during pregnancy 12 , others found a continuous decrease from 10 to 40 weeks 13 or from 17 to 37 weeks 20 , while others still 14 reported that the cervix became longer between 8 and 25 weeks and then shortened. In most studies cervical length did not differ between nulliparous and parous women 13,14,20,28,29 , however in some the cervix was longer in parous women 17,18 . The discrepant results may be explained by differences in measurement technique, study design, the period in gestation studied, the statistical methods used, and the interpretation of the results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Results of other studies are more variable: some found that cervical length did not change during pregnancy 12 , others found a continuous decrease from 10 to 40 weeks 13 or from 17 to 37 weeks 20 , while others still 14 reported that the cervix became longer between 8 and 25 weeks and then shortened. In most studies cervical length did not differ between nulliparous and parous women 13,14,20,28,29 , however in some the cervix was longer in parous women 17,18 . The discrepant results may be explained by differences in measurement technique, study design, the period in gestation studied, the statistical methods used, and the interpretation of the results.…”
Section: Discussionmentioning
confidence: 94%
“…The discrepant results may be explained by differences in measurement technique, study design, the period in gestation studied, the statistical methods used, and the interpretation of the results. For example, in some studies 13,15,16,19,20,28 a correlation coefficient was used to describe changes in cervical length with gestational age. Only Gramellini et al 13 , Murakawa et al 20 and Brieger et al 15 reported a strong or moderate negative correlation between cervical length and gestational age (r = 0.92, P < 0.001, r = 0.4, P < 0.001 and σ = 0.6, P < 0.001) compared with the other studies 16,19,28 where the negative correlation was weak.…”
Section: Discussionmentioning
confidence: 99%
“…There is a continuous decrease in CL which has a steady drop and then tends to shortenning rate of cervix towards the term [13]. According to gestational agerelated reference values of CL measured by transvaginal ultrasonography, measures of CL at 22-26 weeks of gestation values between 28 and 51 mm (10th-90th percentile) [14]. In our study, CL at 22-26 weeks of gestation was 37.63±6.53 mm among patients who delivered at term.…”
Section: Discussionmentioning
confidence: 49%
“…Our patients are not routinely screened for bacterial vaginosis, so unfortunately we do not have these data to report. With regard to how we calculated cervical length, we do not routinely measure cervical curvature in our ultrasound unit, so we may have underestimated the actual cervical length as reported by Gramellini et al 5 Additionally, we do not routinely measure the internal os dilation. However, neither of these was utilized in the landmark study on cervical length and risk of preterm …”
Section: Replymentioning
confidence: 99%
“…In one study, curvature of the cervix was observed in 48% of 301 women, and increased with cervical length from 0% at less than 16 mm to 25% at 16-25 mm and 51% at 26-55 mm 4 . Gramellini et al 5 measured cervical length in a straight line, if the cervix did not show any curvature. In the presence of cervical curvature, the measurement was broken down into two or more segments.…”
mentioning
confidence: 99%